Diet overlap among top predators at the South Orkney Islands, Antarctica - Bertolin, María Lila; Casaux, Ricardo Jorge (Polar Biology)
In order to understand interspecific trophic relationships between top predators, we analyzed diet information for nine bird and two seal species collected in the austral summer from 1996 to 2000 at South Orkney Islands. Overall, the diet of most of the predators was mainly composed of krill and fish. The percentage of re-occurrence of prey among predators ranged from 25.3 to 36.7, and fish, krill and squid re-occurred most frequently. The re-occurrence of fish among predator pairs ranged from 8.1 to 28.1. The species that re-occurred most frequently were the nototheniid fishes Gobionotothen gibberifrons, Nototheniops nudifrons and Nototheniops nybelini, and the myctophid Electrona antarctica. Prey overlap was greatest between Chinstrap (Pygoscelis antarctica) and Adélie (Pygoscelis adeliae) Penguins. Most predator pairs had high overlap of fish prey species. Predators that could forage on demersal and water column prey had yearly variable diets. This variability may be explained by fluctuations in krill availability. In years when krill is scarce (e.g. 2000), these predators diversify their diet by increasing the consumption of fish, which increases the re-occurrence of these preys in the diets. Our samples suggest the recovery of G. gibberifrons stocks around the South Orkney Islands and draw attention to the potential increase of interspecific food competition between predators under scenarios of decreasing krill availability. This information can be used to identify the ecological consequences of fluctuations in krill availability and aid in the management of krill fisheries. Fil: Bertolin, María Lila. Ministerio de Relaciones Exteriores, Comercio Internacional y Culto. Direccion Nacional del Antártico; Argentina Fil: Casaux, Ricardo Jorge. Centro de Investigación Esquel de Montaña y Estepa Patagónica (CIEMEP) CONICET-UNPSJB; Argentina